UPAYA MENINGKATKAN KEMAMPUAN MEMBACA MENGGUNAKAN MEDIA CERITA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS II SD SWASTA AN-NUR TANJUNG MORAWA - Akalia, Pinky; Sujarwo, Sujarwo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading is a learning process that can produce knowledge and insight from the information sources read. Reading ability is the basis for mastering various fields of study. If children at early school age do not immediately have reading skills, they will have difficulty in learning various fields of study in the following classes. This study aims to improve reading skills by using illustrated story media in the Indonesian Language subject of grade II Elementary School students. The research method used in this study is Classroom Action Research. The research was conducted in the first semester of the 2023/2024 academic year in three cycles, each cycle having two meetings. The subjects of this study were grade 2 Elementary School students totaling 20 students, namely 12 boys and 8 girls. The data collection techniques used were tests, observations, and documentation. While the data collection instrument used oral tests and student observation sheets. Data analysis was carried out descriptively qualitatively. Illustrated story media can improve the reading skills of grade 2 students of An-Nur Tanjung Morawa Private Elementary School with the acquisition of student observation scores that have increased from cycle I to cycle III and have obtained scores. In cycle I there was an increase with an average value of 65.1, in cycle II there was an increase with an average value of 73.7, and in cycle III there was an increase with an average value of 88.05. The completion in cycles I, II and III also increased from 60%, to 70% to 90%.